2006
DOI: 10.1086/504934
|View full text |Cite
|
Sign up to set email alerts
|

Improved Clinical Outcome of Patients With Candida Bloodstream Infections Through Direct Consultation by Infectious Diseases Physicians in a Japanese University Hospital

Abstract: The introduction of an active system of IDP consultation for every case of Candida BSI in our hospital substantially improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
4
26
0
Order By: Relevance
“…It is reported that performing consultations on infectious diseases leads to a reduction in inadequate antibiotic therapy. 25,26 Our results are concordant with those of Doern et al 6 in the significant reduction observed in the total number of microbiological and biochemical tests performed on patients of the intervention group. This decrease can be attributed to having rapidly reported microbiological results, thus enabling physicians to act sooner and avoiding unnecessary diagnostic and complementary clinical tests as glucose and C-reactive protein determinations.…”
Section: Discussionsupporting
confidence: 91%
“…It is reported that performing consultations on infectious diseases leads to a reduction in inadequate antibiotic therapy. 25,26 Our results are concordant with those of Doern et al 6 in the significant reduction observed in the total number of microbiological and biochemical tests performed on patients of the intervention group. This decrease can be attributed to having rapidly reported microbiological results, thus enabling physicians to act sooner and avoiding unnecessary diagnostic and complementary clinical tests as glucose and C-reactive protein determinations.…”
Section: Discussionsupporting
confidence: 91%
“…Minimization of SSI can be achieved by refinement of surgical technique 8 and direct consultation by infectious disease physicians. 16,28 Because the majority of gram-positive Enterococci and gram-negative rods in our center were previously reported to be resistant to flomoxef, which was used for postoperative prophylaxis in our center, broaderspectrum prophylaxis, if implemented, should be reassessed continually with respect to the potential for emergence of increasing antimicrobial resistance (to the prophylactic agents used). 20,29,30 Initial reports from our center and others 7,8,20,23,25,27 indicated that Candida was the most common fungal infection after LT. Those results are in accordance with our present study results.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of fungal species was done in accordance with standard methods, 15 and antifungal susceptibility tests and interpretative breakpoints in accordance with US National Committee for Clinical Laboratory Standards approved standard M27-A2. 16 …”
Section: Protocol For Examinations Of Bacterial and Fungal Infectionsmentioning
confidence: 99%
“…Given that a past study reported improved mortality in patients with candidemia by AST intervention with an IDP,4 the IDP's clinical judgment may be the most important aspect of improving the prognosis in patients with candidemia. Therefore, more discussion is needed regarding why the AST without an IDP did not improve mortality despite improving adherence to the guidelines for managing candidemia.…”
mentioning
confidence: 99%